2014
DOI: 10.1007/s10456-014-9438-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of VEGF pathway genes in six randomized phase III trials assessing the addition of bevacizumab to standard therapy

Abstract: This large genetic analysis suggests that variants in VEGF-A, EPAS1, IL8RA, VHL, and VEGF-C have potential value in predicting bevacizumab treatment outcome across tumor types. Although these associations did not survive correction for multiple testing in a genotype-by-interaction analysis, they are among the strongest predictive effects reported to date for genetic variants and bevacizumab efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 53 publications
3
37
0
1
Order By: Relevance
“…Only a meta-analysis from six randomized phase III trials evaluating bevacizumab-treated patients diagnosed of six different types of tumors includes 59 cases of renal cancer, and a non-significant association was found [20].…”
Section: Bevacizumab and Sorafenibmentioning
confidence: 98%
“…Only a meta-analysis from six randomized phase III trials evaluating bevacizumab-treated patients diagnosed of six different types of tumors includes 59 cases of renal cancer, and a non-significant association was found [20].…”
Section: Bevacizumab and Sorafenibmentioning
confidence: 98%
“…Although mechanistic explanations of the contribution of polymorphisms to disease progression and/or treatment response are not always available, they are a useful tool to select patients that will maximally benefit from therapy (de Haas et al, 2014) or predict adverse side effects (Lambrechts et al, 2014). Van der Veldt et al (2011) studied polymorphisms of genes involved in sunitinib pharmacokinetics, and variations in the drug-converting enzyme CYP3A5 and efflux transporter ABCB1 were associated with enhanced progression-free survival in sunitinib-treated patients with metastatic renal cell cancer.…”
Section: F Emerging Mechanisms Of Resistancementioning
confidence: 99%
“…41 A recent study showed that variable expression of VEGF-A, VHL, and VEGF-C along with other genes may predict the efficacy of bevacizumab. 15 Other molecular markers or factors are probably also important in regulating the therapeutic efficacy of bevacizumab. Both anti-VEGF and anti-HIF1a treatments have shown limited efficacy in managing intracranial tumors and have not yet been fully investigated for hemangioblastomas.…”
Section: Hemangioblastomasmentioning
confidence: 99%